PENINGKATAN AKTIVITAS NUMERASI BILANGAN CACAH MELALUI STAD BERBANTUAN SMART NUMBER BOARD PADA SISWA KELAS V - Adiamsa, Putra; Sri Hariani, Lilik; Ma’rifatika, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy competence is one of the fundamental skills that elementary school students must develop to support problem solving in everyday life. However, numeracy instruction on whole number concepts in Grade V continues to face several challenges, including low student participation in learning activities, limited peer interaction, and the suboptimal use of instructional media. These conditions have resulted in numeracy activities that have not yet reached the expected level. This study aimed to improve students' whole number numeracy activities through the implementation of the Student Teams Achievement Division (STAD) learning model assisted by the Smart Number Board. The research employed a Classroom Action Research (CAR) design conducted in two cycles involving 17 Grade V students of SD Negeri Gadang 2 Malang during the 2025/2026 academic year. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected through observations of students' numeracy activities and documentation. The findings revealed that the average numeracy activity increased from 56.43% in the pre-cycle to 73.21% in Cycle I and further improved to 88.57% n Cycle II. These results indicate that the implementation of the STAD learning model assisted by the Smart Number Board effectively enhanced students' engagement in whole number numeracy learning. Therefore, the STAD model integrated with the Smart Number Board can serve as an effective instructional alternative for improving numeracy activities among elementary school students.